A Complex Puzzle : Realities of English-speaking Seniors in Quebec - Bell, Shannon (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
Ideally, we would grow old in good health, maintaining physical and mental well-being and enjoy social inclusion and economic security in a respectful and supportive environment. However, despite strategies to build toward such an ideal in the face of an aging population, public policy and programs at all levels of government largely continue to be shaped by the needs of younger generations. This brief looks at challenges that Quebec’s English-speaking seniors face. It draws on research and policy efforts aimed at understanding and improving the aging experience in the province.

The Newsletter of the Yellow Door / L'Infolettre de la Porte Jaune - Yellow Door (2024)
Number of pages: 13

February 2024 eBulletin - McGill Community For Lifelong Learning (MCLL) (2024)
Number of pages: 6

CHSSN Senior Wellness Centre Initiative Activity Report - Year 2 : 2022-2023 - Community Health and Social Services Network (CHSSN) (2024)
This community initiative supports 30 English-speaking organizations to implement face-to face and virtual health promotion activities to isolated English-speaking seniors in 76 sites across Quebec. The main goal of these centres is to break down social isolation, increase access to information in English, and increase autonomy and well-being through purposeful programming.

Brief for Consultations with the Secrétariat aux relations avec les Québécois d’expression anglaise - Seniors Action Quebec (SAQ) (2024)

Initiative de bien-être pour les aînés du CHSSN rapport d'activité : 2023-2024 - Community Health and Social Services Network (CHSSN) (2024)

Senior Wellness Centre Initiative Activity Report : 2022-2023 - Community Health and Social Services Network (CHSSN) (2024)

Senior Wellness Centre Initiative Activity Report : 2023-2024 - Community Health and Social Services Network (CHSSN) (2024)

December 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)
Number of pages: 6

November 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)
Number of pages: 9

[Newsletter] - 4 Korners Family Resource Center (2023)
Number of pages: 14

Seniors Action Quebec E-Newsletter - Seniors Action Quebec (SAQ) (2023)
Number of pages: 11

[Newsletter] - 4 Korners Family Resource Center (2023)
Number of pages: 10

[Newsletter] - 4 Korners Family Resource Center (2023)
Number of pages: 13

June 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)
Number of pages: 10

E-Newsletter - Seniors Action Quebec (2023)
Number of pages: 10

Seniors Action Quebec Presentation on Study Matters Relating to Minority-Language Health Services - Seniors Action Quebec (SAQ) (2023)

May 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)
Number of pages: 7

VISION : Bulletin for health and wellbeing - Vision Gaspé-Percé Now (2023)
Number of pages: 2

Seniors Action Quebec Brief : Vieillir et vivre ensemble, chez soi, dans sa communauté, au Québec (VVE) - Plan d’action 2024-2029 - Seniors Action Quebec (SAQ) (2023)

April 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)
Number of pages: 9

E-Newsletter - Seniors Action Quebec (2023)
Number of pages: 10

Access to Justice in English Project : Senior Care Services in English in Quebec : Executive Summary of Final Report and Recommendations to the Ministry of Health and Social Services - Quebec Community Groups Network (QCGN) (2023)

Make the Case Report : Access to Senior Care in English in Quebec : A research analysis of English language rights in Quebec health care and access to the SAPA program for English-speaking seniors in Quebec - Quebec Community Groups Network (QCGN) (2023)
This report discusses and details one of the AJEQ Project’s candidate issues of research: access to senior health care services in English in Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.

Access to Justice in English Project : Senior Care Services in English in Quebec - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English Project (“the AJEQ Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec. The second issue studied by the Project was access to health care services for seniors in English through Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.
Parallel title : Executive Summary of Final Report and Reccomendations to the Ministry of Health and Social Services

Senior Care Services in English in Quebec : Executive Summary of Final Report and Recommendations of the Ministry of Health and Social Services - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English Project (“the AJEQ Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec. The second issue studied by the Project was access to health care services for seniors in English through Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.

CHSSN Senior Wellness Centre Initiative Activity Report Year 2 (2022-2023) - Community Health and Social Services Network (CHSSN) (2023)

Senior Wellness Centre Initiative Activity Report (2022-2023) - Community Health and Social Services Network (CHSSN) (2023)

Spring 2023 : MCLL News - McGill Community For Lifelong Learning (MCLL) (2023)
Number of pages: 8

Annual Report 2022-2023 - Seniors Action Quebec (SAQ) (2023)

The Yellow Door : 2022-2023 Annual Report / La Porte Jaune : 2022-2023 Rapport annuel - Yellow Door (2023)

December 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 12

E-Newsletter - Seniors Action Quebec (SAQ) (2022)
Number of pages: 7

Partners in Health - Centre for Access to Services in English (CASE) (2022)
Number of pages: 4

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)
Number of pages: 2

E-Newsletter - Seniors Action Quebec (SAQ) (2022)
Number of pages: 9

The Yellow Door Celebrates 50 Years of the Generations Program - Yellow Door (2022)

Seniors Action Quebec Welcomes Additional Support for Seniors and for the English-speaking Community Announced in Quebec Budget - Seniors Action Quebec (SAQ) (2022)

Fraud : What you should know - Assistance and Referral Centre (ARC) (2022)

Videoconferencing with Older Adults : Best Practices for Psychosocial Group Interventions - Aubin, Ginette; Larivière, Nadine; Marcoux, Lyson; Couture, Mélanie; Charbonneau, Hélène (Community Health and Social Services Network, 2022)
This document presents an overview of the recommended practices for videoconferencing with older adults in the framework of psychosocial group interventions.

Improving the Health and Well-being of English-speaking Seniors in the Laurentians, Québec : A Needs Assessment - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
This needs assessment was commissioned by the 4Korners Laurentian Community Network, a registered Canadian charitable organization founded in 2005, which connects individuals of the Laurentians with programs and services to meet their needs in a secure and inclusive environment. The objective was to identify the needs of the aging English-speaking population in the Laurentians and to determine if they are currently being met. The First Nations Adult Education School Council conducted the assessment in partnership with S.O.A.R. Solutions, a consulting firm. The work was overseen by a committee (the Seniors’ Needs Assessment Committee, SNAC), made up of 4Korners employees, volunteers, the Elders’ Community Worker from the Kanesatake Health Center and project consultants from the First Nations Adult Education School Council.

Senior Safety Plan : Raising Awarness of Elder Abuse on the Lower North Shore - Maurice, Jenna; Kippen, Kayla (Coasters Association, 2022)

Impact Report 2021-2022 - 4Korners (2022)

English : an Asset! - Réseau de l’est de l’île pour les services en anglais (REISA) (2022)
Parallel title : Health and Social Social Service : Working with English- speaking Communities Montreal's East and North

2021-2022 : Annual Report / Rapport annuel - Seniors Action Quebec (SAQ) (2022)

2021-2022 Annual Report - The English Speaking Catholic Council (2022)

The Yellow Door : 2021-2022 Annual Report / La Porte Jaune : 2021-2022 Rapport annuel - Yellow Door (2022)

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 13

E-Newsletter - Seniors Action Quebec (SAQ) (2021)
Number of pages: 13

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 19

Press Release : A Celebration in Song, Spoken Word & Step Final Episode of We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Making Homemade Tomato Sauce with Greg on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 16

Press Release : Author Conversations with Richard King on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Organic Gardening with Hannah on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 16

E-Newsletter - Seniors Action Quebec (SAQ) (2021)
Number of pages: 9

Press Release : Urban Art with Jamie on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Tango Dancing with Mireille & Friends on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 18

Press Release : Making Jam with Susan on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : The Flamboyant World of Drag with Barbada on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Community Organization of Lanaudière (ECOL) (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 15

E-Newsletter - Seniors Action Quebec (SAQ) (2021)
Number of pages: 7

Press Release : Wine Pairing with Ana on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

World Elder Abuse Awareness Day : Well-Treatment in All Circumstances - Michaud, Julie (2021)

Press Release : Horse Therapy with Karine on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Indigenous Hoop Dancing with Makhena on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 16

Chateauguay / Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2021)
Number of pages: 4

Press Release : Bird Watching with Joël Coutu on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Eating Healthy on a Budget with Crystal on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 16

Press Release : Animal Fostering with Cindy on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Spring Special! Gardening in Small Spaces on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 14

[Letter of Support re: Fulford Residence] - Celani, Paula; The English Speaking Catholic Council (ESCC) (2021)

Press Release : Flower Arranging on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Laughter Yoga on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 20

E-Newsletter - Seniors Action Quebec (SAQ) (2021)
Number of pages: 6

Press Release : New Episode of Web Series for Seniors We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : New York Times Bestselling Author Louise Penny Is The Guest of the Web Series for Seniors We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 18

Press Release : Celebrated New York Times Bestselling Author Louise Penny, on Senior’s Web Series We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 27

Vaudeuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2021)
Number of pages: 4

Impact Report 2020-2021 - 4Korners (2021)

Annual Report 2021 - Committee for Anglophone Social Action (CASA) (2021)

Community NetLink - Community Health and Social Services Network (CHSSN) (2021)
Number of pages: 6

McGill Community For Lifelong Learning : Fall 2021 - McGill Community For Lifelong Learning (MCLL) (2021)

Understanding the Experience of English-speaking Seniors in Quebec : Accessing and Interacting with Health and Social Services and the Effect on Health Outcomes - Recreo Therapy (Community Health and Social Services Network (CHSSN), 2021)

2020/2021 Annual Report - Seniors Action Quebec (SAQ) (2021)

2020-2021 Annual Report - The English Speaking Catholic Council (ESCC) (2021)

The Yellow Door : 2020-2021 Annual Report / La Porte Jaune : 2020-2021 Rapport annuel - Yellow Door (2021)

The Yellow Door : Frequently Asked Questions - Yellow Door (2021)

The Yellow Door Press Kit - Yellow Door (2021)

Press Release : A Holiday Concert of Quebec Performers at Martha Wainwright's URSA Follows Incredibly Popular First Episode of "We're All In This Together" - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 27

Press Release : Launch of Project We Are All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 27

E-Newsletter - Seniors Action Quebec (SAQ) (2020)
Number of pages: 8

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 23

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2020)
Number of pages: 2

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 22

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Newsletter - Seniors Action Quebec (SAQ) (2020)
Number of pages: 8

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 14

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

10 Innovative Projects to Assist Vulnerable English-speaking Youth and Seniors - Quebec Community Groups Network (QCGN) (2020)

Reisaction : Our Response to Covid-19 - Réseau de l’est de l’île pour les services en anglais (REISA) (2020)
Number of pages: 11

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 11

Deconfinement Guidelines : What You Should Know in Times of Crisis - Seniors Action Quebec (SAQ) (2020)

4Korners Activities ONLINE - 4 Korners Family Resource Center (2020)
Number of pages: 18

Newsletter - Seniors Action Quebec (SAQ) (2020)
Number of pages: 4

4Korners Activities ONLINE - 4 Korners Family Resource Center (2020)
Number of pages: 18

Seniors Action Quebec Statement on Situation at Residence Herron - Seniors Action Quebec (SAQ) (2020)

4Korners April 2020 - 4 Korners Family Resource Center (2020)
Number of pages: 10

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

QCGN Welcomes Positive Measures for English-speaking Seniors - Quebec Community Groups Network (QCGN) (2020)

Chateauguay/The Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Impact Report 2019-2020 - 4Korners (2020)

Covid-19 : Considerations When Deciding to Move Seniors from Residences or CHSLDS - Seniors Action Quebec (SAQ) (2020)

Tips on Helping Seniors Deal with Isolation During Covid-19 Pandemic - Seniors Action Quebec (SAQ) (2020)

What to Ask a Senior's Residence During the Covid-19 Pandemic - Seniors Action Quebec (SAQ) (2020)

The Yellow Door : 2019-2020 Annual Report - Yellow Door (2020)

$1.1 Million Fund to Address Needs of Vulnerable English-speaking Youth and Seniors - Quebec Community Groups Network (QCGN) (2019)

August 2019 4K Newsletter - 4 Korners Family Resource Center (2019)
Number of pages: 6

June 2019 4K Newsletter - 4 Korners Family Resource Center (2019)
Number of pages: 7

Community Matters - Montérégie West Community Network (MWCN) (2019)
Number of pages: 4

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2019)
Number of pages: 4

May 2019 4K Newsletter - 4 Korners Family Resource Center (2019)
Number of pages: 5

2018-2019 Annual Report - Voice of English-speaking Quebec (VEQ) (2019)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)
Number of pages: 6

Report on the Consultation with the English-speaking Seniors of Laval - Pocock, Joanne (AGAPE, 2019)
This report was done in anticipation of the Laval Regional Access Committee who’s mandate is to give advice on the health and social services access program developed by the Centre intégré de santé et de services sociaux de Laval (CISSS Laval) in accordance with sections 348 and 510 of the Act respecting health and social services. The Regional Access Committee evaluates the access program and, if necessary, suggests modifications. The committee provides an opinion on the modalities of application, monitoring and evaluation of the regional access program. Additionally, the committee gives an opinion to the CISSS de Laval on the priority needs of the region’s English-speaking clientele in terms of accessibility to health and social services in the English language. Finally, the committee makes recommendations regarding promotional and awareness activities related to accessibility of services in the English language.

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)
Number of pages: 7

Evaluation of Community Services for English-speaking Seniors in Gaspé-Magdalen Islands - Richardson, Mary; Brown, Cathy; Burke, Helena; Synnott, Jessica (Community Health and Social Services Network (CHSSN), 2019)
This evaluation was undertaken by request of all three organizations. It follows an earlier evaluation completed in 2013 covering a smaller number of activities, by the same author. The evaluation was designed to take into account a) information on the wellness sessions (content, attendance, frequency, etc.); b) the perspectives of seniors; and c) the perspectives of the facilitators (workers). The following sources of information were used: a) attendance records; b) an online survey filled out in January-March 2019 by 141 seniors; and c) interviews conducted by the author, virtually, in February 2019 with seven facilitators and outreach workers.
Keywords: Official Language Minority Community (OLMC)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)
Number of pages: 8

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)
Number of pages: 6

Impact Report 2018-19 : English Community Services & Support - 4Korners (2019)

Promoting the Health and Well-being of English-speaking Seniors in Quebec : A Community Model - Community Health and Social Services Network (CHSSN) (2019)

Promoting the Health and Well-being of English Speaking Seniors in Quebec : A Community Model - Kueber, Russell; Pocock, Joanne; Hobbs-Robert, Jennifer; Hale, Jeffery (Community Health and Social Services Network (CHSSN), 2019)
This document describes a community model for improving the health and well-being of a linguistic minority senior population in Quebec. English-speaking seniors have unique challenges due to language barriers, socioeconomic inequalities as well as the lack of awareness of their needs and lack of representation associated with the minority status of their community. Many community organizations have recognized the critical level of vulnerability of this population and have designed and implemented successful strategies to address these challenges while remaining aligned with the Quebec government's comprehensive strategies and approaches on healthy aging such as Vieillir et vivre ensemble and Municipalite amie des aines. The main purpose of the document is to help inform and guide English-speaking communities and their community and public partners in their ongoing collaborative efforts to effectively adapt programs and services to improve the lives of English-speaking seniors in their communities.

Message For Our Veterans - Maurice, Cornella (2019)

Social Initiatives for Vulnerable English-speaking Youth Seniors Newcomers / Initiatives sociales pour jeunes aînés nouveaux arrivants - Quebec Community Groups Network (QCGN) (2019)
The Community Innovation Fund (CIF) has helped Quebec’s English-speaking communities transform social innovation into action through the development of skills. The Fund financed 10 innovative projects that targeted particular needs and priorities of vulnerable English-speaking youth, seniors and newcomers. Each project, in its own way, served to improve job skills or help maintain basic socio-economic security of English-speaking Quebecers. In the following pages, you will learn more about these projects – what they set out to do, what they’ve accomplished and how they served to enhance the vitality of English-speaking Quebec.
Keywords: Official Language Minority Community (OLMC)

Health and Social Service Resources for the English-speaking Seniors in the East end of Montreal - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)

The Yellow Door : 2018-2019 Annual Report - Yellow Door (2019)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 7

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 8

Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)
Number of pages: 3

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 8

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 9

Semaji - Black Community Resource Centre (BCRC) (2018)
Number of pages: 10

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 7

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 8

Semaji - Black Community Resource Centre (BCRC) (2018)
Number of pages: 11

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 10

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 7

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 8

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 8

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 8

Impact Report 2017-18 : English Community Services & Support - 4Korners (2018)

Message For Our Veterans - Maurice, Cornella (2018)

Health and Social Service Resources for the English-speaking Seniors in the East end of Montreal - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)
Number of pages: 7

9 Quick Safety Tips to Manage Your Medications - Trimble, Johanna; Currie, Janet (2018)

Annual Report 2017-2018 - Voice of English-speaking Quebec (VEQ) (2018)

The Yellow Door : 2017-2018 Annual Report - Yellow Door (2018)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 8

Forecaster - Coasters Association (2017)
Number of pages: 6

Improving the Spectrum of Services Offered to English-Speaking Seniors : CIUSSS de la Capitale-Nationale’s Experience Implementation Project: 2014-2018 - Paquette, Brigitte (2017)
issued: November 23, 2017/November 24, 2017 Number of Pages : 35

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 8

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 10

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 8

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 9

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 6

LAURENTIANS NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 7

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)
Number of pages: 4

LAURENTIANS NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 8

Annex - List of Funded Projects - Quebec Community Groups Network (QCGN) (2017)

Social Initiatives to Address Needs of Vulnerable English-speaking Youth, Seniors and Newcomers - Quebec Community Groups Network (QCGN) (2017)

LAURENTIANS NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 5

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 6

A Needs Assessment : Better Understanding the Current Situation of the Senior Population - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Magdalen Islanders (CAMI), 2017)
This needs assessment was conducted as part of a community development process in the English-speaking community of Grosse-Ile, on the Magdalen Islands, Quebec. It is part of the follow- up to a community portrait that was developed through a participatory process in early 2015. The process involved the mobilization and engagement of a number of local stakeholders as well as community residents who expressed their views on a number of different themes. One of the issues that was highlighted by community members as a concern, even a priority, was that of the aging population within the ESC, having access to few services and limited support for caregivers.
Parallel title: Improving the Health and Well-Being of English-Speaking Magdalen Islanders
Keywords: Official Language Minority Community (OLMC)

Welcome to Saint Brigid’s Home Residential and Long Term Care Center : Welcome Guide for Residents and their Loved Ones - Jeffery Hale - Saint Brigid's (JHSB) (2017)

Access to Public Long-term Care : Useful information for seniors and their loved ones - Jeffery Hale Community Services (2017)

LAURENTIANS NEWSLETTER - 4 Korners Family Resource Center (2017)
Number of pages: 7

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)
Number of pages: 2

Répit et soutien aux aides-soignant / Respite and Support for Caregivers - Coasters Association (2017)

Health and Social Service Resources for the English-speaking Seniors in the East end of Montreal - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)
Number of pages: 7

Annual Report 2016-2017 - Voice of English-speaking Quebec (VEQ) (2017)

[Newsletter] - 4 Korners Family Resource Center (2016)
Number of pages: 8

Community Innovation Fund Seeking Proposals to Better Serve Vulnerable Youth, Seniors/Caregivers or Newcomers in Quebec's English-language Communities - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

[Newsletter] - 4 Korners Family Resource Center (2016)
Number of pages: 8

[Newsletter] - 4 Korners Family Resource Center (2016)
Number of pages: 9

[Newsletter] - 4 Korners Family Resource Center (2016)
Number of pages: 7

[Newsletter] - 4 Korners Family Resource Center (2016)
Number of pages: 7

[Newsletter] - 4 Korners Family Resource Center (2016)
Number of pages: 8

English-speaking Quebecers to Benefit from Investment Fund for Official Language Minority Communities - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

[Newsletter] - 4 Korners Family Resource Center (2016)
Number of pages: 6

Building Community Capacity From Evidence to Action (2015-2016) - Pocock, Joanne (2016)

[Newsletter] - 4 Korners Family Resource Center (2016)
Number of pages: 6

[Newsletter] - 4 Korners Family Resource Center (2016)
Number of pages: 5

2015-2016 Funded Projects - Dialogue McGill (2016)

Socio-demographic Profile of the Population Aged 65 and Over - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Est-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Estrie – CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l-Ouest-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Gaspèsie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS des Îles - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS des Îles - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Centre-Ouest-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Centre-Sud-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Nord-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Saguenay – Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Focus Group Findings 2015-2016 - Seniors Action Quebec (SAQ) (2016)

English-speaking Seniors : RTS de l'Estrie - CHUS - Townshippers' Association (2016)

Community Profile : Senior and Youth - Vision Gaspé-Percé Now (VGPN) (2016)
This document is a resource for community and government organizations and for those who may benefit from information on the senior and youth English-speaking populations of Gaspé. Production of this document was made possible by the financial support of Health Canada and the demographic data has been provided by the Community Health and Social Services Network (CHSSN).

[Newsletter] - 4 Korners Family Resource Center (2015)
Number of pages: 4

[Newsletter] - 4 Korners Family Resource Center (2015)
Number of pages: 4

[Newsletter] - 4 Korners Family Resource Center (2015)
Number of pages: 4

Semaji - Black Community Resource Centre (BCRC) (2015)
Number of pages: 9

Building Community Capacity From Evidence to Action (2015-2016) : Profile of English-speaking Seniors : CLSC Manicouagan - Pocock, Joanne (Seniors Action Quebec (SAQ), 2015)
The Seniors Action Québec (SAQ) project is designed to mobilize English-speaking (ES) seniors (65+) and their communities in four regions of the province (Gaspésie, Greater Quebec City, Outaouais and the North Shore). This will be done by creating a network among English language regional community organizations to amplify the voice of minority language seniors and enhance their contribution to the vitality of their communities. The project will ready the network to identify critical issues affecting English-speaking seniors, establish regional action plans to address seniors’ priorities and to generally promote awareness of provincial and regional organizations serving the interests of the 65 years and over age group.

Building Community Capacity From Evidence to Action (2015-2016) : Profile of English-speaking Seniors : CLSC Territoire Naskapi - Pocock, Joanne (Seniors Action Quebec (SAQ), 2015)
The Seniors Action Québec (SAQ) project is designed to mobilize English-speaking (ES) seniors (65+) and their communities in four regions of the province (Gaspésie, Greater Quebec City, Outaouais and the North Shore). This will be done by creating a network among English language regional community organizations to amplify the voice of minority language seniors and enhance their contribution to the vitality of their communities. The project will ready the network to identify critical issues affecting English-speaking seniors, establish regional action plans to address seniors’ priorities and to generally promote awareness of provincial and regional organizations serving the interests of the 65 years and over age group.

Building Community Capacity From Evidence to Action (2015-2016) : Profile of English-speaking Seniors : CSSS de La Côte-de-Gaspé - Pocock, Joanne (Seniors Action Quebec (SAQ), 2015)
The Seniors Action Québec (SAQ) project is designed to mobilize English-speaking (ES) seniors (65+) and their communities in four regions of the province (Gaspésie, Greater Quebec City, Outaouais and the North Shore). This will be done by creating a network among English language regional community organizations to amplify the voice of minority language seniors and enhance their contribution to the vitality of their communities. The project will ready the network to identify critical issues affecting English-speaking seniors, establish regional action plans to address seniors’ priorities and to generally promote awareness of provincial and regional organizations serving the interests of the 65 years and over age group.

Building Community Capacity From Evidence to Action (2015-2016) : Profile of English-speaking Seniors : Rocher-Percé - Pocock, Joanne (Seniors Action Quebec (SAQ), 2015)
The Seniors Action Québec (SAQ) project is designed to mobilize English-speaking (ES) seniors (65+) and their communities in four regions of the province (Gaspésie, Greater Quebec City, Outaouais and the North Shore). This will be done by creating a network among English language regional community organizations to amplify the voice of minority language seniors and enhance their contribution to the vitality of their communities. The project will ready the network to identify critical issues affecting English-speaking seniors, establish regional action plans to address seniors’ priorities and to generally promote awareness of provincial and regional organizations serving the interests of the 65 years and over age group.

Message For Our Veterans - Maurice, Cornella (2015)

Blazing a Trail for Active and Healthy Aging: An Action Plan for Quebec’s English-speaking Seniors 2010-2015 / Tracer la voie pour vieillir en santé et demeurer actif : Plan d’action à l’intention des aînés d’expression anglaise du Québec 2010-2015 - Quebec Community Groups Network (QCGN) (2015)

[VISION AGM Report] - Vision Gaspé-Percé Now (2015)

Moving Forward : Building Research Capacity Related to Quebec's English-speaking Seniors - Quebec Community Groups Network (QCGN) (Quebec Community Groups Network (QCGN), 2014)
We are grateful to the Government of Quebec who funded the project through the Soutien aux initiatives visant le respect des aînés (SIRA) program. We’d like to acknowledge the project Steering Committee who demonstrated ongoing dedication and commitment to the project. Members are: David Cassidy, president of Seniors Action Quebec and committee co-chair; Sylvia Martin-Laforge, director general at QCGN and committee co-Chair; Cheryl Henry-Leggo, Vision Gaspé-Percé Now; Kevin Erskine-Henry, chair, South Shore Community Partners Network; Premela Pearson, secretary, Indian Women’s Circle; Jim Colmer, residepnt, James Colmer Consultation Inc; Jan Anderson-Toupin, Jeffery Hale; Al Abdon, Filipino Association of Montreal and Suburbs. The QCGN contracted Dr. Joanne Pocock as the lead researcher on this project. The project has deeply benefited from her guidance, professionalism and intellectual rigour.
Keywords: Official Language Minority Community (OLMC)

QCGN Launches Most up-to-date, Detailed Portrait of Quebec's English Speaking Seniors - Quebec Community Groups Network (QCGN) (2014)

Building Communities Together : Laurentians, Outaouais, Quebec Region - Seniors Action Quebec (SAQ) (2014)

Moving Forward : Building Research Capacity Related to Quebec’s English-speaking Seniors : Executive Summary - Quebec Community Groups Network (QCGN) (2014)
While Quebec’s English-speaking seniors share many of the same needs and priorities as their French-speaking counterparts, as an official linguistic minority community (OLMC) they also have needs and priorities that are unique within the broader senior population. While there has been a great deal of research on Quebec’s demographic shift and its senior population, little - if - any attention has been paid to the specific needs and priorities of Quebec’s English-speaking seniors who are an official language minority community in Canada. One notable exception is the recent 2013 report entitled ‘Enjoying your senior years in your own language’ for the Office of the Commissioner for Official Languages, which employed 2006 Canadian census figures.

[VISION AGM Report] - Vision Gaspé-Percé Now (2014)

Federal Institutions Must Properly Support Quebec's English-speaking Seniors, says Graham Fraser - Office of the Comissioner of Official Languages (2013)

English-speaking Seniors Unite to Create Provincial Vote - Seniors Action Quebec (2013)

Jeffery Hale - Saint Brigid's at a Glance - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Fall Prevention : Information for Clients and Their Families - Jeffery Hale - Saint Brigid's (JHSB) (2013)

English-speaking Seniors in Quebec - Canada. Office of the Commissioner of Official Languages (2013)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)
Number of pages: 6

[VISION AGM Report] - Vision Gaspé-Percé Now (2013)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)
Number of pages: 6

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)
Number of pages: 6

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)
Number of pages: 6

Specialized Geriatric and Psychogeriatric Consultation Team - Jeffery Hale - Saint Brigid's (JHSB) (2011)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2011)
Number of pages: 4

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2011)
Number of pages: 6

Blazing a Trail for Active and Healthy Aging : An Action Plan for Quebec English-speaking Seniors / Tracer la voie pour vieillir en santé et demeurer actif : Plan d’action à l’intention des aînés d’expression anglaise du Québec - Quebec Community Groups Network (QCGN) (2009)
In 2007, the Ministère de la Famille et des Aînés conducted public consultations across all 17 regions to assess the living conditions of seniors and to identify their major challenges across Quebec. The roving consultations looked at a variety of subjects including the role and needs of family caregivers, home support services, intergenerational solidarity, abuse of and violence towards seniors, as well as the contributions that seniors make to society. It demonstrated the importance of understanding the needs and priorities of seniors as their numbers gradually increase in proportion to the rest of the population due to enhanced longevity. The findings of the consultations were summarized by Minister Marguerite Blais, assisted by Mrs. Sheila Goldbloom and Dr. Réjean Hébert in a report entitled “Public Consultation Report on Living Conditions of Quebec: Preparing the Future with our Seniors,” which identified the priorities for all seniors in Quebec. En 2007, le ministère de la Famille et des Aînés a mené une consultation publique dans 17 régions afin d’évaluer les conditions de vie des aînés et d’établir leurs principaux enjeux dans tout le Québec. Cette commission itinérante a permis d’examiner une variété de sujets, notamment le rôle et les besoins des aidants naturels, les services de soutien à domicile, la solidarité intergénérationnelle, les abus et la violence envers les aînés ainsi que la contribution des aînés à la société. Cet exercice a démontré l’importance de comprendre les besoins et les priorités des aînés car, en raison de l’accroissement de la longévité, leur nombre augmente graduellement, proportionnellement au reste de la population. Les conclusions de ce processus de consultation ont été résumées par la ministre Marguerite Blais, en collaboration avec Mme Sheila Goldbloom et le Dr Réjean Hébert, dans un ouvrage intitulé Rapport de la consultation publique sur les conditions de vie des aînés : Préparons l’avenir avec nos aînés. Ce rapport définit les priorités de tous les aînés du Québec.

Health Matters - Coasters Association (2007)
Number of pages: 20

Seniors are an Asset for Quebec - Lincoln, Clifford (2007)

Public Consultation on Seniors' Living Conditions : A Social Issue That is the Responsibility of Us All Quebecers - The English Speaking Catholic Council (ESCC) (2007)
The English Speaking Catholic Council would like to congratulate the Government of Quebec for recognizing the importance of issues related to seniors and an aging population and its establishment of the post of Minister Responsible for Seniors. We also welcome the initiative of Mme Marguerite Blais, the Minister Responsible for Seniors, to hold public hearings on seniors’ living conditions in Quebec, an issue on which our community and its institutions serving the elderly have considerable experience and great concern.

Respect Minority and Community Rights in Any Health Care Reforms - The English Speaking Catholic Council (ESCC) (2004)

Remembering our Heritage and Culture - Fequet Griffin, Priscilla (Coasters Association, 2003)
The project started on June 16, 2003, at which time a schedule of activities was produced (see annex 1). Following this, a list of all seniors (65 and up), within the Municipality of Bonne Esperance, was developed containing their ages and phone numbers (see annex 2). All seniors were contacted for their participation in this project, in which all ninety-nine were willing to take part.

The McGill Institute for Learning in Retirement (MILR) : By-laws - The McGill Institute for Learning in Retirement (MILR) (1996)

Celebrating Caregivers - Coasters Association

Partnering to Meet the Growing Needs of English-Speaking Seniors During the Pandemic - Council for Anglophone Magdalen Islanders (CAMI)

Comité de résidents Saint Brigid’s Residents’ Committee : Bienvenue chez vous ! Welcome to Your Home! - Jeffrey Hale - Saint Brigid's (JHSB)

Socio-demographic Profile of the Population Aged 65 and Over - Province of Québec - Pocock, Joanne (Community Health and Social Services Network)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French- speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Literacy Across the Curriculumedia Focus - Shohet, Linda
Number of pages: 5

Executive Summary : The English Speaking Catholic Council’s Response to Public Consultation on Seniors’ Living Conditions - The English Speaking Catholic Council (ESCC)
For the English Speaking Catholic Council (ESCC), the care of seniors, especially the frail elderly, is a moral and social imperative for us all. Our community has created a number of specialized institutions and services over the past one hundred and fifty years that allow us to carry out our responsibilities to seniors, but Quebec faces many challenges if we want to protect and promote fully the interests of older citizens.

Wellness Centre for Seniors - Vision Gaspé-Percé Now

Services Available for Seniors in the Gaspé-Barachois Area - Vision Gaspé-Percé Now (VGPN)

The Many Faces of Elder Abuse - Voice of English-speaking Quebec (VEQ)
Voice of English-speaking Québec is proud to support English-speaking seniors in the greater Quebec City region. This booklet was produced to help seniors in our community stay independent, safe and to help prevent abuse and discrimination targeting them. This project is funded in part by Service Canada under the New Horizons for Seniors Program.